High-resolution X-ray absorption spectrometry of atomic vapors - Mihelič, Andrej (Acta chimica slovenica, 2004)
A measurement of an x-ray absorption spectrum of a monatomic sample yields pure atomic absorption essential for the EXAFS (Extended X-ray Absorption FineStructure) analysis in cases of a weak structural signal. A construction of an absorption cell to contain vapor sample takes into account specific properties of the investigated element. Metal-vapor absorption cells for the elements K, zn, Rb, Cd, Cs, and Hg are presented and comments are made on the use of materials and the operating mechanisms of the cells.
Keywords: atomska absorpcija; EXAFS; kovine; podaljšana drobna struktura rentgenskih absorpcijskih robov